Antitumor effect of a new nano-vector with miRNA-135a on malignant glioma - Liang C (Dove Medical Press, 2017)
Chaofeng Liang,1,* Weitong Sun,2,* Haiyong He,1,* Baoyu Zhang,1 Cong Ling,1 Bocheng Wang,1 Tengchao Huang,1 Bo Hou,1 Ying Guo1 1Department of Neurosurgery, 3rd Affiliated Hospital of Sun Yat-sen University, Sun Yat-sen University, Guangdong, China; 2The Pharmaceutical College of Jiamusi University, Jiamusi University, Jiamusi, China *These authors contributed equally to this work Introduction: MiR-135a is found to selectively induce apoptosis in glioma cell but not in normal neurons and glial cells. However, low transfection efficacy limits its application in vivo as other miRNAs. We prepared a new kind of nano-vector based on polyethylene glycol methyl ether (mPEG) and hyper-branched polyethylenimine (hy-PEI) in order to improve the miRNA delivery system into the glioma cells. Methods: The mPEG-g-PEI/miR-135a was constructed and detected by 1H NMR and FTIR analyses. Transmission electron microscope was utilized for its characteristics. Stability and release efficiency was assessed by electrophoresis. Biocompatibility was observed and analyzed through co-culture with astrocytes and malignant glioma cells (C6). Transfection rate was monitored by laser confocal microscopy and flow cytometry. The antitumor effect of mPEG-g-PEI/miR-135a to C6 was confirmed in vivo by MR scanning, pathology and survival curve. RT-PCR was used to assay transfection efficiency of mPEG-g-PEI/miR-135a in vitro and in vivo. And Western blotting was used to assess the expressions of the targeted proteins of miR-135a.Results: In this experiment, we found the optimal N/P ratio of mPEG-g-PEI/miR-135a was about 6 judged by Zeta potential, particle size and encapsulation ability. The stability of mPEG-g-PEI/miR-135a in serum and the release efficiency in acid(pH=5.0) of mPEG-g-PEI/miR-135a were simulated the environment in vivo and in tumor. The mPEG-g-PEI nano-vector was co-cultured with malignant glioma cell C6 and normal astrocytes in vitro and showed good biocompatibility evaluated by CCK8 assay. The cell experiments in vitro indicated that mPEG-g-PEI could significantly improve miR-135a transfection by enhancing uptake effect of both normal glial and glioma cells. Given the C6 implanted in situ model, we discovered that the mPEG-g-PEI/miR-135a could obviously increase the survival period and inhibit the growth of glioma confirmed by MRI and histochemistry. In addition, the transfection efficiency of mPEG-g-PEI was better than that of other transfection agents either in vitro or in vivo confirmed by RT-PCR. Moreover, the expressions of the targeted proteins of miR-135a were consistent with the in vitro results. Conclusion: These results suggest that mPEG-g-PEI is expected to provide a new effective intracellular miRNA delivery system with low toxicity for glioma therapy. Keywords: nano-vector, miRNA-135a, malignant glioma, gene delivery, Micro RNA